2008
DOI: 10.1007/s12237-008-9079-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Macrobenthic Fauna in a Tropical Hypersaline Coastal Lagoon in Ghana, West Africa

Abstract: The macrobenthic fauna in the large, hypersaline, shallow Keta lagoon in Ghana was sampled at 20 stations in the wet (September 2002) and dry seasons (March 2003) to elucidate the effects of abiotic factors on community patterns. The macrobenthic fauna was low in density and species diversity and numerically dominated by bivalves and capitellid polychaetes. These organisms appear able to withstand physical disturbance (when lagoon water levels become extremely low) and osmotic stress (when salinities are ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 32 publications
3
25
2
Order By: Relevance
“…The temperature range determined for the Fosu Lagoon was similar to results obtained by Lamptey and Armah (2008) for the Keta Lagoon. Aquatic plant species are dependent on growth conditions, particularly temperature, organic loading, oxygen status and nutrient availability.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The temperature range determined for the Fosu Lagoon was similar to results obtained by Lamptey and Armah (2008) for the Keta Lagoon. Aquatic plant species are dependent on growth conditions, particularly temperature, organic loading, oxygen status and nutrient availability.…”
Section: Resultssupporting
confidence: 84%
“…Most importantly, the systems under study (Fosu and Benya) differ significantly in mouth status and salinity, which can also explain the obtained for the Keta Lagoon. However, this was not true of conductivity, which was much higher in this study compared to the results of Lamptey and Armah (2008). Although the Keta Lagoon is considered to be an open lagoon, it is effectively closed for most of the year and is therefore similar to the Fosu Lagoon.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…The animal abundance in the hypersaline lakes of the Crimea can be high (Table 3), which means that animal species play an important role in the trophic chains of these waters (Balushkina et al, 2009). In other regions, similar observations have been made (Kokkinn, Williams, 1988;Wurtsbaugh, 1992;Lamptey, Armah, 2008;Amarouayache et al, 2012;Carrasco, Perissinotto, 2012 (Khomenko, 2003;Khomenko, Shadrin, 2009). Zagorodnyaya et Kolesnikova et al, 2008;Kolesnikova et al, 2017 Artemia spp.…”
Section: Animal Abundance and Possible Applicationssupporting
confidence: 70%
“…Similarly, the correlation made between environmental parameters against diversity components revealed that the parameters such as, wind speed, pH, salinity, DO, carbonate, DOC and silt had significant positive correlation with diversity, while other parameters were showing weak correlation with evenness (J) and richness (d). True to this, earlier reports by Lamptey and Armah [70]; Sivaraj et al [71]; Murugesan et al [14] proven that stable environmental parameters like increased pH, temperature, salinity, DO and high intensity of light penetration during summer are responsible for its positive relationship with diversity. Further, CCA results clearly indicated the significant association of the polychaete species with many environmental parameters.…”
Section: Discussionmentioning
confidence: 85%